2015
DOI: 10.3390/rs70404565
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Space-Borne Hyperspectral Data for Biomass Quantification in an Arid Environment: Advantages and Limitations

Abstract: Abstract:In spite of considerable efforts to monitor global vegetation, biomass quantification in drylands is still a major challenge due to low spectral resolution and considerable background effects. Hence, this study examines the potential of the space-borne hyperspectral Hyperion sensor compared to the multispectral Landsat OLI sensor in predicting dwarf shrub biomass in an arid region characterized by challenging conditions for satellite-based analysis: The Eastern Pamirs of Tajikistan. We calculated vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Like the chlorophyll content, biomass is another challenging biophysical index for Hyperion in heterogeneous environments such as low vegetation cover areas [87,88]. The same observation was made for S2 data [89].…”
Section: Preliminary Analysis Of the Literature Databasementioning
confidence: 49%
See 1 more Smart Citation
“…Like the chlorophyll content, biomass is another challenging biophysical index for Hyperion in heterogeneous environments such as low vegetation cover areas [87,88]. The same observation was made for S2 data [89].…”
Section: Preliminary Analysis Of the Literature Databasementioning
confidence: 49%
“…Results with HyspIRI were slightly above those of S2 because of the higher spectral resolution and the narrower bandwidth of the hyperspectral sensor, but they both revealed comparable performances. Nonetheless, Hyperion data provided better results than multispectral sensors for discriminating between NPV and soil (i.e., ETM+ sensor) [88] or for estimating indices capturing the SWIR spectral region (i.e., OLI sensor) [87]. Agricultural studies also pointed out that Hyperion is useful to detect crop residues thanks to the SWIR region that is sensitive to lignin and cellulose [92,93].…”
Section: Preliminary Analysis Of the Literature Databasementioning
confidence: 99%
“…This makes Sentinel 2 an interesting alternative to commercial satellites like RapidEye in the context of woody biomass estimations in semi-arid areas [95]. In addition, hyperspectral satellite data may reduce model uncertainties for satellite-based vegetation analysis in drylands, as the higher spectral resolution is more capable in capturing the non-photosynthetic part of wood plants [27].…”
Section: Model Uncertaintiesmentioning
confidence: 99%
“…Image texture discriminates the spatial variability of neighboring pixels independent from image tone [35]. The review of existing scientific literature has shown that little research has been conducted and published on biomass or wood volume estimation in semi-arid regions using high resolution imagery in combination with indices, including the red edge band or texture attributes, e.g., [10,27,36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation